Stability analysis, control of simple chaotic system and its hybrid projective synchronization with fractional Lu system - Yadav V.K.; Shukla V.K.; Srivastava M.; Das S. (My University, 2025)
In this article, the stability analysis and chaos control of Simple chaotic system have been discussed. A new lemma based on Caputo derivative is used during the stability analysis of the fractional order Simple chaotic system through Lyapunov stability theory. During hybrid projective synchronization the Simple chaotic system is considered as drive system and Lu chaotic system is taken as response system. Nonlinear control method has been used to analyse the hybrid projective synchronization of fractional systems. For numerical simulations Adams-Bashforth-Moulton method has been used and results obtained are presented graphically. © 2020 L&H Scientific Publishing, LLC.